2008
DOI: 10.1002/ptr.2461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pine bark extract (Pycnogenol®) on symptoms of knee osteoarthritis

Abstract: Results show that Pycnogenol in patients with mild to moderate OA improves symptoms and is able to spare NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 17 publications
3
53
0
1
Order By: Relevance
“…This promising trial in a very common disease effecting millions of people needs further studies with large number of patients. Cisar et al (2008) studied the effect of PBE on knee osteoarthritis stages I and II in a double-blind, placebo-control trial treating 100 patients with 150 mg/day PBE for three months. After that patients filled the WOMAC questionnaire every 2 weeks reporting any change in the use of previously prescribed anti-inflammatory medication during the study period.…”
Section: Osteoarthritis and Pbementioning
confidence: 99%
“…This promising trial in a very common disease effecting millions of people needs further studies with large number of patients. Cisar et al (2008) studied the effect of PBE on knee osteoarthritis stages I and II in a double-blind, placebo-control trial treating 100 patients with 150 mg/day PBE for three months. After that patients filled the WOMAC questionnaire every 2 weeks reporting any change in the use of previously prescribed anti-inflammatory medication during the study period.…”
Section: Osteoarthritis and Pbementioning
confidence: 99%
“…In the context of treatment of OA, inhibition of matrix metalloproteases (MMPs) is of great interest. After the intake of Pycnogenol ® , release of MMP9 from macrophages is inhibited (Cisar et al, 2006), thus blocking the destructive activity of MMP on cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…and 3 other species) was performed using 5 investigated compounds and 12 selected peaks(peak No. 2,3,4,6,7,10,15,17,20,23,26,29, were bold in Table 1 ) as markers respectively (shown in Figure 5 ). Their results were very similar, which sort all samples into two clusters, Abies holophylla Maxim.…”
Section: Hierarchical Clustering Analysis (Hca)mentioning
confidence: 99%
“…Pine needle was first recorded in "Compendium of Materia Medica", and is widely used in China for treatment of rheumatism and joint pain (Raynal, 2007, Cisar et al, 2008, swelling and pain from injuries, night blindness, hypertension, neurasthenia and external use in treating chilblain (Meng et al, 2012, Suntar et al, 2012, Clark et al, 2014. Phytochemical studies showed abundant compounds presented in pine needle, such an essential oil, flavonoids, Shikimic acid, amino acids, lignin , Kwon et al,2010, Zhang and Wang, 2010, among which essential oil were considered to be the primary bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%